Analisis Semiotika Film ? - Prasojo, Dading (Jurnal The Messenger, 2014)
In this research, the writer concluding the result of what he found from of the movie. Begins from the conflict that happened between Chinnese Ethnic and indirinous people, the creator want to present in this movie and also want to show the problems between Islam and Christian. The creator want to make a thought that among religions should be toulerant and live peacefully just like what in film.But there is the scene that research the meaning of tolerance it self. The scene where Surya (Agus Kuncoro) who chosen asa Jesus. According to researcher, the creator of this movie want to show the tolerance among religions, but actually it seems like decreasing of the meaning of tolerance it self. In this case, mixture religions shouldn t be happened, because the tolerance among religions prevealing in public life not religions ritualials like that.In thus case, the movie creator want to make a thought to the people about public live among religions and intracultural. Baut the researcher saw his case contrary to myth that precealing about how sensitive when we talk about religion to different relilious faith. The researcher assumed this as dimytologies, because not suitable with the myth that developed in public.